Impact of age and comorbidities on short- and long-term outcomes of patients undergoing surgery for colorectal cancer - Turri, Giulia; Caliskan, Gulser; Conti, Cristian; Martinelli, Luigi; De Giulio, Ernesto; Ruzzenente, Andrea; Guglielmi, Alfredo; Verlato, Giuseppe; Pedrazzani, Corrado (Frontiers in Oncology, 2022)
Background: As the world population is progressively ageing, more and more elderly patients will require cancer surgery. Although curative surgery is the treatment of choice for resectable colorectal cancer (CRC), it is still debated whether elderly frail patients should undergo major cancer surgery due to the increased risk of postoperative and long-term mortality. The aim of this retrospective study was to evaluate the impact of age and comorbidities on postoperative mortality/morbidity and long-term outcome, looking for potential age-related survival differences. Methods: 1482 patients operated for CRC at our institution between January 2005 and October 2020 were analysed. The independent effect of age and comorbidities on postoperative complications was assessed by a logistic model, while the effect on overall survival (OS) and cancer-related survival (CRS) was estimated by a Cox regression model. Results: Median age in the cohort was 67.8 years. Postoperative mortality was very low in the whole cohort (0.8%) and contained even in older age groups (3.2% in patients aged 80-84 years, 4% in the 85-90 years age group). Cumulative incidence of postoperative complications was doubled in patients with comorbidities (32.8% vs. 15.1%, p=0.002). With regards to OS, as expected, it exponentially decreased with advancing age. Conversely, differences in CRS were less pronounced between age groups, and absent in patients with stage 0-I CRC. Analysis of all causes and cancer-related mortality revealed a peak within 2 years from surgery, suggesting a prolonged impact of surgery. In patients aged 75 years and above, all causes mortality showed a steep increase 1 year after surgery, while cancer-related mortality plateaued at about 4 years after surgery. On multivariable analysis OS, but not CRS, was significantly influenced by age. Conclusions: Although acceptable results of surgery in elderly patients, OS is strongly dependent on age: older people die more from competing causes than cancer related treatments compared to younger age classes. Preoperative identification of risk factors for low OS may help the selection of those elderly patients who would benefit from curative CRC surgery.